IDEOLOGICAL ATTITUDES OF LITHUANIAN BIBLIOPHILIA AND ITS ORGANIZATIONAL STRUCTURE IN THE SOVIET PERIOD - LIEPAITĖ, INGA (Knygotyra, 2012)
The aim of the article is to reveal the ideological attitudes and organizational structure of Lithuanian bibliophilia of the end of the 5th–9th decades. Alongside with the term bibliophilia as we understand it today, the term mass bibliophilia is also used in the article. The latter allows to identify precisely the attitude of the Soviet ideologists towards bibliophilia, which was inculcated officially (via the press and formal activities of certain organizations) as ostensibly a mass phenomenon that has passed from an exclusive and narrow to an open and broad space (in terms of quantity) and this conditioned distortion of traditionally understood essence of bibliophilia (in terms of quality). Mass bibliophilia is an elementary liking for books, collecting books and love of books. The development of Lithuanian bibliophilia in the Soviet times may be divided into two periods: 1) preorganizational, which lasted from 1940 when the Society of XXVII Book Lovers was closed, to 1974 when the Voluntary Society of Book Friends of Lithuanian SSR was founded, and 2) organizational. In the first period, already during the German occupation, there were discussions about the revival of official activities of the mentioned XXVII Book Lovers’ Society. In 1959, Romualdas Šalūga for the first time brought the idea in the press about the need to establish a book lovers’ society; however, although the idea was noticed, it was not realized at that time. There are archival and other sources that may imply wide non-formal professional ties between bibliophiles approximatelyfrom the second half of the 6th decade. In the period 1970–1975, on the initiative of the same R. Šalūga, a Vilnius book friends’ club was functioning, combining bibliophilic and cultural-cognitive activities. In the second stage of bibliophilia development, an important role fell to the Voluntary Society of Book Friends of Lithuanian SSR, established in 1974. The latter was perceived by its founders as a mass public bibliophilic organization. The Society was later criticized for bureaucracy and artificiality of its activities; nevertheless, it is important to accentuate that it was this society that capacitated legal activities of the book friends’ club from 1975. Rather often book friends’ clubs were used as means for cultural matters. Due to the fragmentary coverage of the activities of such clubs and shortage of their archives it is difficult to say at the moment how many book friends’ clubs, apart from the Vilnius Mažvydas and Plungė Daukantas clubs, were (or if they ever were) of bibliophilic profile. The activity of the two latter clubs, were not equal, either. It was impacted by both external (cultural politics carried on by the Soviet regime in Lithuania) and internal factors (who was a chairperson, affinity of members’ interests, etc.). Those clubs played an important role in the history of Lithuanian bibliophilia, and they are the only ones that continue their activities since the Soviet time up to now.
Keywords: ...